Virome specific to tick genus with distinct ecogeographical distribution - Di Tian; Run-Ze Ye; Yu-Yu Li; Ning Wang; Wan-Ying Gao; Bai-Hui Wang; Zhe-Tao Lin; Wen-Jie Zhu; Qiu-Shi Wang; Ya-Ting Liu; Hua Wei; Yi-Fei Wang; et al. (Microbiome)
Abstract Background The emergence of tick-borne pathogens poses a serious threat to both human and animal health. There remains controversy about virome diversity in relation to tick genus and ecogeographical factors. Results We conducted the meta‑transcriptomic sequencing of 155 pools of ticks encompassing 7 species of 3 genera collected from diverse geographical fauna of Ningxia Province, China. Two species of Dermacentor genus were distributed in the predominantly grassland areas of the central and eastern regions, with the lowest viral diversity. Two species of Hyalomma ticks were found in the predominantly desert areas of the northern regions, with intermediate viral diversity. Three species of Haemaphysalis ticks were concentrated in the predominantly forested areas of the southern regions, exhibiting the highest viral diversity. We assembled 348 viral genomes of 63 species in 14 orders, including 26 novel viruses. The identified viruses were clearly specific to tick genus: 22 virus species were exclusive to Dermacentor, 12 to Hyalomma, and 27 to Haemaphysalis. Conclusions The associations between tick genera and geographical distribution, viral richness, and composition provide new insights into tick-virus interactions, offering clues to identify high-risk regions for different tick-borne viruses. Video Abstract